A case of desmoplastic fibroma occurring at the mandible: Serial observations suggesting the successful effects of antihistamine agent and interaction of estrogen hormone. Issue 3 (May 2017) - Makita, Hiroki; Hatakeyama, Daijiro; Yonemoto, Kazuhiro; Kato, Keizo; Kato, Hiroki; Shibata, Toshiyuki
Abstract: Long term follow up case of desmoplastic fibroma (DF) occurring at the left mandible was reported. A 27-year-old female was referred to our department with chief complaints of spontaneous pain and swelling of her left mandible. Physical examination revealed the asymmetric enlarged jaw and swelling of the left mandible covering with normal mucosa, though sensory neuropathy was not observed. Image examinations showed multifocal osteolytic lesions in the osteosclerotic mandible. To define the diagnosis, an enucleation of the lesions and pathological analysis were carried out. Pathological diagnosis of DF was made and further analysis revealed the presence of degranulation of mast cells and estrogen receptor β expressing cells in the specimens. We carried out curettage and chemotherapy using tranilast possessing the inhibitory effects on the mast cell activity. This surgical treatment was not successful, but the lesions were reduced by the tranilast administration and were maintained within the acceptable level during 3 years of this administration period and following 5 months just before pregnancy. The lesions were aggravated during the pregnancy period that was high estrogen condition and spontaneously disappeared after delivery.